A study on psychosocial problems among adolescents in urban slums in Kolkata, West Bengal - Sinha Roy, Amal Kumar; Sau, Manabendra; Madhwani, Kishore P.; Das, Pausali; Singh, Jitendra Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: Puberty is the unique stage of growth and development associated with the social and psychological changes referred to as adolescence. The adolescent psychosocial development is the process through which the dependent child becomes a self reliant adult. A large number of adolescents suffer from psychosocial problems and many of these problems are of transient in nature and are often not even noticed. The objective of the study was to find out the prevalence of psychosocial problems among adolescents. Methods: A cross-sectional study was conducted in ward no 58 of Tangra area of Kolkata. The study group comprised of 420 adolescents, selected by multistage stratified random sampling. Data was collected on a pre-designed and pre-tested questionnaire by interviewing the adolescents and was subsequently analyzed by using suitable statistical package. Results: Anxiety was maximum (34.76%) in adolescent boys whereas conduct disorder was found to be maximum (28.57%) in adolescent girls. Majority (35.62%) of late adolescent boys were attributed to substance abuse. Anxiety was found to be the commonest problem among adolescent males in all religions. Educational difficulties were maximum among Muslim adolescents. The problems per subject (with psycho-social problems) were more in adolescent boys (4.4) and girls (3.8) having joint family. None of the class I adolescent girls claimed to have any educational difficulties. Conclusions: A holistic approach to underlying causes of psycho-social problems of adolescents should be undertaken. There is need of strengthening the existing “package” of services for adolescents in various initiatives and programmes.